2020
DOI: 10.1021/acsmacrolett.9b00872
|View full text |Cite
|
Sign up to set email alerts
|

Porous Ru(bpy)32+-Linked Polymers for Recyclable Photocatalysis of Enantioselective Alkylation of Aldehydes

Abstract: Two metal porous organic polymers (POPs) that contain the [Ru(bpy) 3 ] 2+ cores are prepared via one-pot Suzuki−Miyaura coupling reactions. Both Ru-POPs are thermally stable at up to 340 °C in air and do not dissolve in all solvents tested. One of the POPs has been revealed to be highly effective and reusable as a heterogeneous photocatalyst for visible light-driven enantioselective alkylation of aldehydes. After 10 cycles, the catalyst still maintains the enantioselectivity, while the activity just decreases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 46 publications
1
19
0
Order By: Relevance
“…48 Very recently, Li, Zhang, and co-workers demonstrated the activities of iridium and ruthenium complex-linked porous organic polymers for recyclable, broad-scope photocatalytic organic transformations. 49,50 These advances proved the conceptual feasibility of the applications of noble metal complex-incorporated polymer-supported photocatalysts toward challenging organic transformations. However, the current studies just focused on the incorporation of photocatalysts into the backbones of cross-linked polymers; it is hard to attain some complicated and important organic transformations, e.g., some kinds of cross-coupling reactions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…48 Very recently, Li, Zhang, and co-workers demonstrated the activities of iridium and ruthenium complex-linked porous organic polymers for recyclable, broad-scope photocatalytic organic transformations. 49,50 These advances proved the conceptual feasibility of the applications of noble metal complex-incorporated polymer-supported photocatalysts toward challenging organic transformations. However, the current studies just focused on the incorporation of photocatalysts into the backbones of cross-linked polymers; it is hard to attain some complicated and important organic transformations, e.g., some kinds of cross-coupling reactions.…”
Section: Introductionmentioning
confidence: 99%
“…In 2018, Han and co-workers reported that cationic polycarbazole networks cross-linked by an [Ir­(ppy 2 )­(bpy)] + (ppy, phenylpyridine; bpy, 2,2′-bipyridine) unit could serve as photosensitizers for the oxidation of sulfides, hydroxylation of arylboronic acids, and cross-dehydrogenative coupling reactions . Very recently, Li, Zhang, and co-workers demonstrated the activities of iridium and ruthenium complex-linked porous organic polymers for recyclable, broad-scope photocatalytic organic transformations. , These advances proved the conceptual feasibility of the applications of noble metal complex-incorporated polymer-supported photocatalysts toward challenging organic transformations. However, the current studies just focused on the incorporation of photocatalysts into the backbones of cross-linked polymers; it is hard to attain some complicated and important organic transformations, e.g., some kinds of cross-coupling reactions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… [29] Aldehydes with alkyl chains, in the presence or absence of olefins, aromatic rings, or carbamates at their α‐positions reacted with α‐bromocarbonyl compounds bearing a wide variety of electron‐withdrawing functional groups to afford the desired products in 63–91 % yields with excellent enantioselectivities (88–99 % ee). Numerous different conditions were subsequently devised for this transformation using different photocatalysts such as Fe(bpy) 3 2+ , [68] organic dyes, [69–70] metal‐organic frameworks (MOF), [71–72] semiconductor‐based catalysts, [73–76] and more recently, Ru‐based polymers [77] and covalent organic frameworks (COF) [78]…”
Section: Photochemical Reactions Involving Enamine/iminium Ion Catalysismentioning
confidence: 99%
“…[ 78 ] Although CMPs have been used as photocatalysts in a variety of photocatalytic reactions such as photo‐oxidation, Suzuki coupling, hydrogen evolution, and so on, [ 79 ] their application in asymmetric photocatalysis is not reported yet, and only a related study was recently published by Zhang and co‐workers (Figure 6b). [ 80 ] To be specific, the conjugated polymers Ru‐POPs catalysts were synthesized via one‐pot Suzuki–Miyaura coupling reaction between tetrakisphenylmethane borate and tris(bipyridine)ruthenium(II) (Ru(bpy) 3 2+ )‐derived bromides. Both Ru‐POPs were amorphous solids and insoluble in common polar solvents, and they displayed strong visible light absorption that afforded them to be good candidates for heterogeneous photocatalysts.…”
Section: Emerging Porous Materialsmentioning
confidence: 99%